Development of SNAP-tag based nanobodies as secondary antibody mimics for indirect immunofluorescence assays - Sheng, Wenjie; Zhang, Chaoyu; Mohiuddin, T. M.; Al-Rawe, Marwah; Schmitz, Roland; Niebert, Marcus; Konrad, Lutz; Wagner, Steffen; Zeppernick, Felix; Meinhold-Heerlein, Ivo; Hussain, Ahmad Fawzi; Justus Liebig University Giessen (My University, 2025)
The immunofluorescence assay is widely used for cellular biology and diagnosis applications. Such an antigen–antibody detection system enables the assessment and visualization of the expression and localization of target proteins. In the classical indirect immunofluorescence assay, secondary antibodies are conjugated to fluorophores. However, conventional secondary antibodies have limited applications due to their large size (150 kDa). Moreover, as animal-derived products, secondary antibodies are associated with ethical concerns and batch-to-batch variability. In this study, we developed fluorescence-labeled recombinant nanobodies as secondary antibodies by utilizing previously established anti–mouse and anti–rabbit IgG secondary nanobodies in combination with the self-labeling SNAP-tag. Nanobodies, which are significantly smaller (15 kDa), are capable to detect primary antibodies produced in mice and rabbits. The SNAP-tag (20 kDa) enables site-specific binding of various O6-benzylguanine (BG)-modified fluorophores to the recombinant nanobodies. These recombinant nanobodies were produced using mammalian cell expression system, and their specific binding to mouse or rabbit antibodies was validated using flow cytometry and multi-color fluorescence microscopy. The low cost, easy of expression, purification and site-specific conjugation procedures for these anti–mouse and anti–rabbit IgG secondary nanobodies make them an attractive alternative to traditional secondary antibodies for indirect immunofluorescence assays.
Keywords: ddc:610